Novel NDUFA12 variants are associated with isolated complex I defect and variable clinical manifestation. Issue 6 (25th March 2021) - Torraco, Alessandra; Nasca, Alessia; Verrigni, Daniela; Pennisi, Alessandra; Zaki, Maha S.; Olivieri, Giorgia; Assouline, Zahra; Martinelli, Diego; Maroofian, Reza; Rizza, Teresa; Di Nottia, Michela; Invernizzi, Federica; et al.
Abstract: Isolated biochemical deficiency of mitochondrial complex I is the most frequent signature among mitochondrial diseases and is associated with a wide variety of clinical symptoms. Leigh syndrome represents the most frequent neuroradiological finding in patients with complex I defect and more than 80 monogenic causes have been involved in the disease. In this report, we describe seven patients from four unrelated families harboring novel NDUFA12 variants, with six of them presenting with Leigh syndrome. Molecular genetic characterization was performed using next‐generation sequencing combined with the Sanger method. Biochemical and protein studies were achieved by enzymatic activities, blue native gel electrophoresis, and western blot analysis. All patients displayed novel homozygous mutations in the NDUFA12 gene, leading to the virtual absence of the corresponding protein. Surprisingly, despite the fact that in none of the analyzed patients, NDUFA12 protein was detected, they present a different onset and clinical course of the disease. Our report expands the array of genetic alterations in NDUFA12 and underlines phenotype variability associated with NDUFA12 defect.